2022
DOI: 10.1080/15476286.2021.2015174
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation of riboswitches in fungi: structural and dynamical insights into TPP riboswitches in Aspergillus oryzae

Abstract: Riboswitches are RNA sensors affecting post-transcriptional processes through their ability to bind to small molecules. Thiamine pyrophosphate (TPP) riboswitch plays a crucial role in regulating genes involved in synthesizing or transporting thiamine and phosphorylated derivatives in bacteria, archaea, plants, and fungi. Although TPP riboswitch is reasonably well known in bacteria, there is a gap in the knowledge of the fungal TPP riboswitches structure and dynamics, involving mainly sequence variation and TPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…[238] The TPP riboswitch is present in fungi and plays a role in the generation and regulation of methionine derivatives in such organisms. Vargas-Junior et al [239] used a computer technique to investigate the structural and dynamic properties of the TPP riboswitch in fungi in order to provide medicinal and biotechnological avenues for addressing the problem of fungal antibiotic resistance.…”
Section: Antibacterial Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…[238] The TPP riboswitch is present in fungi and plays a role in the generation and regulation of methionine derivatives in such organisms. Vargas-Junior et al [239] used a computer technique to investigate the structural and dynamic properties of the TPP riboswitch in fungi in order to provide medicinal and biotechnological avenues for addressing the problem of fungal antibiotic resistance.…”
Section: Antibacterial Targetsmentioning
confidence: 99%
“…In 2007, a regulatory mechanism for the TPP riboswitch in higher plants was proposed by Bocobza et al., indicating that the TPP riboswitch is controlled in the thiamin biosynthesis pathway by variable splicing in the 3”UTR region. [ 70 ] Recent studies have identified the presence of novel TPP riboswitches in various species, including Lactobacillus , [ 71 ] diatoms, [ 72 ] and Aspergillus niger , [ 73 ] which are all widely employed in food production, classification of intestinal bacteria, and the development of antimicrobial drugs.…”
Section: The Classification Of Riboswitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, six riboswitch classes have been identified that sense the levels of coenzyme S -adenosylhomocysteine (SAH) and/or S -adenosylmethionine SAM [ [122] , [123] , [124] ]. In addition to SAM riboswitches, several other riboswitch classes have also been identified as sensors for RNA-derived coenzymes such as Thiamin pyrophosphate (TPP) [ 125 ], flavin mononucleotide (FMN), adenosylcobalamin (AdoCbl), and tetrahydrofolate (THF) [ 119 , 121 , 123 , 126 ]. Members of THF riboswitch class were termed as “folE motif” RNAs.…”
Section: Regulatory Rnas In Bacteriamentioning
confidence: 99%